Tengku Puan of Pahang officially opens ICEWE 2011 - UMP, PNC
The conference attracted more than 200 presenters from Malaysia, Jordan, New Zealand, Pakistan, Nigeria, Thailand, Bangladesh, Iran, Australia, India and United Kingdom and their topics were related to petrochemical, biotechnology, manufacturing, automotive and other industries.